Implementation Of Group Guidance Services To Address Bullying Behavior In Boarding Students - Afriani, Dina; Daulai, Afrahul Fadhila; Daulay, Nurika Khalila (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This study aims to describe the bullying behavior of boarding students at SMA Negeri 2 Plus Panyabung, the implementation of group guidance services in overcoming bullying behavior of boarding students at SMA Negeri 2 Plus Panyabungan, the obstacles in implementing group counseling services in overcoming bullying behavior at boarding students at SMA Negeri 2 Plus Connections and ways to solve obstacles. This study uses a qualitative research type, with a phenomenological approach. Data collection techniques use observation, interviews, and documentation techniques. The results of the study, namely, the bullying behavior of boarding students at SMA Negeri 2 Plus Panyabungan for now is still verbal actions such as backbiting, slandering, gossiping and ostracizing friends, this behavior usually occurs continuously, the implementation of group guidance services at SMA Negeri 2 Plus Panyabungan Teacher BK in SMA Negeri 2 Plus Panyabungan has carried out group guidance service activities in accordance with the needs of students who are in dormitories and those who are not in hostels as well with the theme one of which is bullying behavior which must be above fellow students such as: setting an example of good friends, setting an example so that students can control themselves, the obstacles experienced when carrying out group guidance and how to overcome these obstacles, lack of time when carrying out services and students' non-openness when conveying the problems they experience, how to overcome these obstacles is to try to talk alone with the student so he doesn't feel afraid when conveying the problems experienced by students.